Refractory Complex Crohn’s Perianal Fistulas: A Role for Autologous Microfragmented Adipose Tissue Injection - Laureti, Silvio (Inflamm Bowel Dis, 2020)
BACKGROUND: Complex perianal fistulas represent one of the most challenging manifestations of Crohn’s disease. Combined surgical and medical therapy with biologic drugs today represent the first-line treatment option, but its efficacy does not exceed 60%. Recently, new therapeutic approaches, such as the use of mesenchymal stromal cells, have shown promising results. The adipose tissue is an abundant and easy to access source. The effectiveness, safety, and feasibility of local injections of microfragmented adipose tissue in patients with refractory complex fistulizing perianal Crohn’s disease (PCD) were evaluated. METHODS: Fifteen patients with persistent complex fistulizing PCD after biosurgical approach and subsequent surgical “rescue” repair were treated in S. Orsola-Malpighi Hospital with a single-local administration of microfragmented adipose tissue prepared using a minimal manipulation technique (Lipogems) in a closed system. Clinical outcomes were determined at 24-week follow-ups assessing success rate, defined as combined clinical and radiological remission. RESULTS: Upon clinical examination at 24 weeks, 10 patients had combined remission (clinical and radiographic), 4 patients showed improvements, and 1 patient failed. The results were confirmed in all patients by pelvic MRI. No relevant postoperative complications nor adverse events were reported. CONCLUSION: These results suggest that the local injection of autologous microfragmented adipose tissue is a safe and promising “rescue therapy” for patients with multiresistant complex fistulizing PCD. This approach might be proposed as routine because it is affordable, is minimally invasive, has no risk of sphincteric damage, and can be carried out in a day-surgery setting.